Economies of Scale and Perceived Corruption in Natural Resource Management: A Comparative Study between Ukraine, Romania, and Iceland - Johanna Gisladottir; Sigurbjörg Sigurgeirsdottir; Kristín Vala Ragnarsdóttir; Ingrid Stjernquist (Sustainability, 2021)
The aim of this paper is to enhance understanding of factors that undermine sustainable management of renewable resources by identifying and analyzing the main drivers and dynamics involved, with a focus on the role of corruption perceptions and its implications. To shed light on the research question, we chose to perform a comparative study of three different resource sectors in European countries that are ranked differently on the Corruption Perception Index by Transparency International, namely fisheries in Iceland, forestry in Romania, and arable soils in Ukraine. We conducted 40 in-depth semi-structured interviews with various stakeholders to explore assumptions on individual actions and behavior in the sectors. The interviews were analyzed using a qualitative coding procedure based on causal loop diagrams, a method from system dynamics. The results indicate that even though the cases are different, they share a similar outcome, in that privatization of the resource and consolidation of companies took place, along with perceived risk of both unsustainable resource management practices and corruption. Our findings suggest that the underlying similarities of the cases are that privatization occurred around the same time in early 1990s, when neoliberal economic ideology influentially held up the idea that private ownership meant better management. What followed was a transition to economies of scale that ultimately resulted in dominance of large vertically integrated companies in the sectors. The resulting inequalities between large and small actors in the renewable resource management systems serve to increase the risk for unsustainable management decisions as well as increase perceptions of corruption risks, especially amongst smaller actors in the sectors.